Sustainability capacity of a vegetable gardening intervention for cancer survivors - Mallory G. Cases; Cindy K. Blair; Peter S. Hendricks; Kerry Smith; Scott Snyder; Wendy Demark-Wahnefried (BMC, 2022)
Abstract Background Health behavior interventions, especially those that promote improved diet and physical activity, are increasingly directed toward cancer survivors given their burgeoning numbers and high risk for comorbidity and functional decline. However, for health behavior interventions to achieve maximal public health impact, sustainability at both the individual and organizational levels is crucial. The current study aimed to assess the individual and organizational sustainability of the Harvest for Health mentored vegetable gardening intervention among cancer survivors. Methods Telephone surveys were conducted among 100 cancer survivors (mean age 63 years; primarily breast cancer) completing one-of-two Harvest for Health feasibility trials. Surveys ascertained whether participants continued gardening, and if so, whether they had expanded their gardens. Additionally, surveys were emailed to 23 stakeholders (Cooperative Extension county agents, cancer support group leaders, and healthcare representatives) who were asked to rate the intervention's ability to generate sustained service and produce benefits over time using the eight-domain Program Sustainability Assessment Tool (PSAT). Results The survey among cancer survivors (91.9% response rate) indicated that 85.7% continued gardening throughout the 12 months following intervention completion; 47.3% expanded their gardens beyond the space of the original intervention. Moreover, 5.5% of cancer survivors enrolled in the certification program to become Extension Master Gardeners. The survey among stakeholders generated a similar response rate (i.e., 91.3%) and favorable scores. Of the possible maximum of 7 points on the PSAT, the gardening intervention's "Overall Capacity for Sustainability" scored 5.7 (81.4% of the maximum score), with subscales for "Funding Stability" scoring the lowest though still favorably (5.0) and "Program Evaluation" scoring the highest (6.3). Conclusions Data support the sustainability capacity of the Harvest for Health vegetable gardening intervention for cancer survivors. Indeed, few interventions have proven as durable in terms of individual sustainability. Furthermore, Harvest for Health's overall organizational score of 5.7 on the PSAT is considered strong when compared to a previous review of over 250 programs, where the mean overall organizational PSAT score was 4.84. Thus, solutions for long-term funding are currently being explored to support this strong, holistic program that is directed toward this vulnerable and growing population. Trial registration ClinicalTrials.gov Identifier: NCT02150148